Perceptions and Practices of Mass Bat Exposure Events in the Setting of Rabies Among U.S. Public Health Agencies. (8th July 2016) - Hsu, C. H.; Brown, C. M.; Murphy, J. M.; Haskell, M. G.; Williams, C.; Feldman, K.; Mitchell, K.; Blanton, J. D.; Petersen, B. W.; Wallace, R. M.
Summary: Current guidelines in the setting of exposures to potentially rabid bats established by the Advisory Committee on Immunization Practices (ACIP) address post‐exposure prophylaxis (PEP) administration in situations where a person may not be aware that a bite or direct contact has occurred and the bat is not available for diagnostic testing. These include instances when a bat is discovered in a room where a person awakens from sleep, is a child without an adult witness, has a mental disability or is intoxicated. The current ACIP guidelines, however, do not address PEP in the setting of multiple persons exposed to a bat or a bat colony, otherwise known as mass bat exposure (MBE) events. Due to a dearth of recommendations for response to these events, the reported reactions by public health agencies have varied widely. To address this perceived limitation, a survey of 45 state public health agencies was conducted to characterize prior experiences with MBE and practices to mitigate the public health risks. In general, most states (69% of the respondents) felt current ACIP guidelines were unclear in MBE scenarios. Thirty‐three of the 45 states reported prior experience with MBE, receiving an average of 16.9 MBE calls per year and an investment of 106.7 person‐hours annually on MBE investigations. PEP criteria, investigation methods and the experts recruited in MBE investigations varied between states. These dissimilarities could reflect differences in experience, scenario and resources. The lack of consistency in state responses to potential mass exposures to a highly fatal disease along with the large contingent of states dissatisfied with current ACIP guidance warrants the development of national guidelines in MBE settings.